Alternate vaccine strain selection in the wake of emerging foot-and-mouth disease virus serotype A antigenic variants in India. Issue 23 (31st May 2018) - Mohapatra, Jajati Keshari; Das, Biswajit; Rout, Manoranjan; Sreenivasa, B.P.; Subramaniam, Saravanan; Sanyal, Aniket; Pattnaik, Bramhadev
Highlights: Recent antigenic drift of serotype A FMD field viruses from the Indian vaccine strain. 'r1 ' value of 87 field strains with 8 candidate vaccine strains was determined in VNT. A IND 27/2011 with widest antigenic coverage could be the alternate vaccine strain. It grew to a high titre of log10 7.5 TCID50 /ml in BHK-21 suspension cell culture. Adaptation to suspension cell was accompanied by E82 –K and E131 –K substitution in VP2. Abstract: 'National foot-and-mouth disease (FMD) control programme' is being implemented in India and therefore predicting vaccine match is a key surveillance task. Recently, a considerable proportion of field viruses (75.6%) showed antigenic drift from the existing serotype A vaccine strain A IND 40/2000 necessitating search for an alternate strain. Here, antigenic relationship ('r1 ' value) of 87 field viruses with each of the 8 candidate strains was estimated by virus neutralization test. A IND 27/2011 strain emerged to be the one with the widest spectrum of antigenic coverage showing 'r1 ' value of more than 0.3 with 81.6% of field strains. It achieved a reasonably high titre of log10 7.5 TCID50 /ml in BHK-21 suspension cell which was accompanied by positive charge gaining substitutions (E82 –K and E131 –K in VP2) thought to have adaptive significance. However, potency trial remains to be conducted before A IND 27/2011 finds a place in the vaccine formulation.